Ultraestructura de la cáscara de huevos eclosionados y no eclosionados de Kinosternon angustipons (Testudinata: Kinosternidae - Acuña-Mesén, R (2001)
The ultrastructure of eggshells of Kinosternon angustipons is described and compared with the ones of K. leucostomum and K. scorpioides. Four eggs from captive turtles (30 sections) were studied with Scanning Electron Microscopy (SEM). The shell has three layers: cuticle or external, calcareous or intermediate and testacean or internal. Hatched and non hatched eggs have similar characteristics in their external surface: fanned units and proteic fibers superposed at random. They differ in the presence of spongelike structures and more external porosity in non hatched eggs. The intermediate and testacean layers of the hatched eggs have lance point like spaces and are thin in the proteic fibers. The ultrastructural evidence shows that during the embryonic development the thickness of the peel decreases. Non hatched K. angustipons shells are thicker than in the other two kinosternon species of Costa Rica.